2005
DOI: 10.1371/journal.pcbi.0020134.eor
|View full text |Cite
|
Sign up to set email alerts
|

Targeted molecular dynamics study of C-loop closure and channel gating in nicotinic receptors

Abstract: The initial coupling between ligand binding and channel gating in the human a7 nicotinic acetylcholine receptor (nAChR) has been investigated with targeted molecular dynamics (TMD) simulation. During the simulation, eight residues at the tip of the C-loop in two alternating subunits were forced to move toward a ligand-bound conformation as captured in the crystallographic structure of acetylcholine binding protein (AChBP) in complex with carbamoylcholine. Comparison of apo-and ligand-bound AChBP structures sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 51 publications
5
69
0
Order By: Relevance
“…The global and local conformational change observed in one of the subunits is consistent with previous targeted MD simulations and normal mode analyses (17,18). That these conformational changes correspond to channel opening is supported by SCAM experiments upon agonist binding (10,19).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The global and local conformational change observed in one of the subunits is consistent with previous targeted MD simulations and normal mode analyses (17,18). That these conformational changes correspond to channel opening is supported by SCAM experiments upon agonist binding (10,19).…”
Section: Resultssupporting
confidence: 87%
“…The opposite swings of the C and F loops are reminiscent of the motions seen in the targeted MD simulations of McCammon and coworkers (17). Note that in our simulations, the opposite swings occurred spontaneously, whereas in the study of McCammon and coworkers (17), the motions were triggered by pulling the C loop from the up to the down position, which was supposed to mimic agonist binding. In the cyan subunit, the C loop also moved toward the down position, but the rest of the molecule did not experience additional distortion, leading to the intermediate rmsd shown in Fig.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Subsequent studies, however, attained this goal by exploring energetic coupling among residues within or between subunits by combined mutagenesis studies, single-channel recordings, and thermodynamic mutant cycle analyses (20)(21)(22)(23)(24). These studies revealed that activation of the receptor begins by transition of the C-loop of each α subunit from an opened-up to a closed-in conformation (24)(25)(26); this leads to displacement of β-strand 10, which is contiguous with the pre-M1 domain, and results in conformational changes of the β1-β2 linker and the Cys-loop (Figure 1). Both the β1-β2 linker and the Cys-loop energetically couple with residues in the M2-M3 linker and in the course of channel opening displace the M2 helix away from the center of pore (21,23,27).…”
Section: Introductionmentioning
confidence: 99%